Constellation coordination and pilot reuse for multi‐cell large‐scale MIMO systems. Issue 2 (1st January 2020) - Xu, Fangmin; Wang, Haiquan; Wang, Honggang; Cao, Haiyan
Abstract : To alleviate pilot contamination for multi‐cell large‐scale multiple‐input multiple‐output (MIMO) systems, here the authors propose a constellation coordination scheme according to a constellation coordination constraint (CC constraint) on the large‐scale fading factors. In fact, a detailed analysis of the uplink process introduces the CC constraint, which reveals that if the CC constraint cannot be satisfied, the error probability will be larger than a threshold. Otherwise, the error probability goes to zero if both the number of antennas at the base station and signal‐to‐noise ratio go to infinity. Furthermore, by modelling the location of users as a Poisson point process, the authors derive a safe area threshold according to the CC constraint, through which an adaptive pilot reuse is proposed. In this scheme, users outside the dynamic safe area threshold are allowed to reuse the pilot, while other users are not allowed. Simulation results show that the CC scheme alleviates the pilot contamination effectively and the proposed pilot reuse scheme based on the safe area threshold improves the uplink achievable rate of the system significantly.